Expert system for building cognitive model of a student using 8-puzzle game and for career assessment - Chandra Prakash, V; K. R. Sastry, J; Anusha, K.; Ashok Kumar, P; Venkatesh, N.; Ravi Teja, G. (International Journal of Engineering and Technology, 2018)
Career assessment is useful for a student in order to know the suitable jobs for him/her in future basing on studentâ€™s knowledge memory power, Intelligence, psychological aptitude, etc. During the academic program of a student, it is very important to assess the appropriate career(s), so that a student can select some appropriate electives and some specialized subjects, which lead to an appropriate career(s). In the process of academic program of a student, it is highly essential to plan his/her career. Generally, the career counselor in an institution analyzes the studentâ€™s academic record/Cumulative Grade Point Average (C.G.P.A.) and predicts suitable career(s) in industry. In case of students belonging to Computer Science and Engineering branch, counselor will suggest some appropriate jobs in software industry viz. software designer, software engineer, tester, marketing person, etc. based on the academic record. Apart from academic record, one should also consider the studentâ€™s psychological factors like intelligence, problem solving ability, patience, etc. to predict a better career. We developed an expert system for predicting career by assessing psychological factors of a student like problem solving ability, intelligence and patience levels of a student. In order to assess these psychological factors, we developed 8-puzzle game to assess studentâ€™s intelligence and planning ability levels, fastness in playing game, and patience levels. The system requests the student to play 8-puzzle game many times and displays the scores of student. A career table is designed which consists of list of careers in software industry and the minimum levels of requirements in academic record, intelligence, patience, etc. The academic record and psychological factors of the student are compared with the minimum levels required for each career and thus the system predicts the matching career(s) for the student.Â Â